Identification and Development of Sex Specific DNA Markers in the Ostrich Using Polymerase Chain Reaction - Hinckley, J.D.; Park, R.L.; Xiong, S.; Andersen, W.R.; Kooyman, D.L. (International Journal of Poultry Science, 2005)
The objective of this study was to identify and develop DNA markers that can be used for sex diagnosis in the ostrich (Struthio camelus) using polymerase chain reaction (PCR) technology. DNA was isolated from 15 male and 15 female, year old, crossbred ostriches. Two bulked DNA samples were prepared by grouping sexes. Random amplified polymorphic DNA (RAPD) analysis was used to screen 1400 arbitrary 10-mer primers for polymorphic markers between the bulks. Potential W-linked markers generated with the female bulked DNA sample were confirmed by individual screening of the 30 samples. Five W-linked RAPD markers, UBC388431, UBC4111300, UBC656,120, UBC793687, and OPL 1 7750 were identified by primers UBC388, UBC411, UBC656, UBC793, and OPL-17. Four RAPD markers were chosen for sequence analysis after further screening using 15 male and 12 female, 14-mo-old, birds sexed at slaughter. The sequence data were used to design pairs of specific primers, 18-24 bp, for PCR amplification of individual genomic DNA from 71 birds of varying age (33 males and 38 females). Primers generated reliable female specific sequence characterized amplified regions (SCARS). Four SCARS, ST793677, ST793665, ST4111245, and ST6561023, were developed, which can be used for sex identification in the ostrich. Cross amplification tests were done using male and female genomic DNA from turkeys, domestic animals (cattle, pigs, sheep, horses, and mink), and human. The PCR primers did not generate the sex specific markers in these species, which indicated that the W-linked markers amplified from ostrich genome may be species specific markers. These results demonstrate that RAPD analysis using bulked DNA samples provides an efficient means for the detection of W-chromosome markers in avian species. The SCARS developed can be used for identifying sex in immature ostriches.